2021
DOI: 10.1186/s40729-020-00288-6
|View full text |Cite
|
Sign up to set email alerts
|

Autologous micrografts from the palatal mucosa for bone regeneration in calvarial defects in rats: a radiological and histological analysis

Abstract: Background The application of dental implants is often restricted by bone volume. In such cases, bone grafts are required, although bone graft materials have some disadvantages. Therefore, other effective approaches are needed. Our previous study showed that the autologous micrograft, a dissociated cell suspension made out of palatal connective tissue grafts, promoted bone-marrow cell proliferation and differentiation under osteogenic conditions. In this study, we aimed to evaluate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Data from this study cover the same sample for which a six-month follow-up was published. Previously in-vitro and in-vivo studies on a murine model have demonstrated the effectiveness of the AMGs [18] , [19] . Formerly a case report with a follow-up of three years had been published and demonstrated in a single case the effectiveness of this method in the medium term.…”
Section: Discussionmentioning
confidence: 99%
“…Data from this study cover the same sample for which a six-month follow-up was published. Previously in-vitro and in-vivo studies on a murine model have demonstrated the effectiveness of the AMGs [18] , [19] . Formerly a case report with a follow-up of three years had been published and demonstrated in a single case the effectiveness of this method in the medium term.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the inflammation was quantified by measuring the ratio between the area of blood vessels (mm 2 ) and the total regenerated area (mm 2 ). This last measurement included hard and soft tissue within the location of the defect [ 44 ]. SI-5 contains additional information and specific methods for calculating these variables.…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence values range from 14% to 78% [67]. These differences result from how obesity and OSAS are defined by different authors [68][69][70][71][72][73]. Studies have shown that the degree of obesity and the severity of OSAS are correlated and that adenotonsillary hypertrophy is more common as a risk factor in obese subjects than in the non-obese population with OSAS [18,74,75].…”
Section: Obesitymentioning
confidence: 99%